STATUS KEPEMILIKAN HAK JAMINAN FIDUSIA ATAS HAK JAMINAN YANG DIALIHKAN KE PIHAK LAIN - Attahira, Vellangi; Rahmayani, Nuzul; Syuryani, Syuryani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The researcher discusses the status of ownership of fiduciary security rights over collateral rights transferred to other parties case study (Decision Number 36/Pdt-Bth/2020/PN Bkt). This started when the plaintiff made a unilateral transfer of the object which was the object of collateral, which was known when the defendant was going to pay off the car installments, he received a notification that the car had been paid for by another party. The aim is to find out how the ownership status of the collateral rights over the collateral rights is transferred to other parties and what is the responsibility of the fiduciary recipient for the goods transferred. The form of research conducted by the author is normative. The author of the literature as relevant secondary data, the processing of data analysis carried out is qualitative. So that from this research the results are that the collateral object is transferred without the knowledge of the first party, so it remains that the material rights that are born first will take precedence over those that are born later. However the situation is between the Property Rights and the Law of the contract cannot be overridden by one another, meaning that the Property Rights of an object are still in accordance with the name stated on the Deed or the ownership letter and the responsibility of the fiduciary recipient is obliged to compensate for losses equivalent to the goods transferred.